2019
DOI: 10.1111/jar.12659
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of sedentary behaviour in people with Down syndrome across the lifespan: A clarion call

Abstract: Background Individuals with Down syndrome (DS) experience health disparities possibly associated with high levels of sedentary behaviour (SB). We systematically reviewed SB measurement, levels, patterns, correlates, consequences and interventions in people with DS across the lifespan. Method We searched these databases: Embase; PubMed; Web of Science; Scopus; CINAHL; PsycINFO; SPORTDiscus; and Cochrane Library. We included quantitative studies published in English since 1 January 1990. Results We identified 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…The Genuine League began in 2017, and this is the first time that a Quality of Life survey has been carried out among highly competitive athletes with these characteristics. People with DS are sedentary by definition [17].…”
Section: Discussionmentioning
confidence: 99%
“…The Genuine League began in 2017, and this is the first time that a Quality of Life survey has been carried out among highly competitive athletes with these characteristics. People with DS are sedentary by definition [17].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions may be alleviated or prevented by increasing physical activity and decreasing sedentary behaviour levels (Paul et al 2019). Adults with DS exhibit low levels of physical activity and high levels of sedentary behaviour (Phillips & Holland 2011;Agiovlasitis et al 2020;Oreskovic et al 2020). This knowledge base, however, is not conclusive due to methodological concerns with accelerometer-based measurement of physical activity and sedentary behaviouraccelerometers have not been calibrated for adults with DS.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the findings of studies from Agiovlasitis et al . ( 2020 ) and Esposito et al . ( 2012 ) that revealed that the children and adolescents with ID seem to have higher levels of SB than the general population of peers.…”
Section: Discussionmentioning
confidence: 95%